Synthesis and in silico screening of a library of β-carboline-containing compounds - Brummond, Kay M.; Goodell, John R.; LaPorte, Matthew G.; Wang, Lirong; Xie, Xiang-Qun (Beilstein Journal of Organic Chemistry, 2012)
The synthesis of a library of tetrahydro-β-carboline-containing compounds in milligram quantities is described. Among the unique heterocyclic frameworks are twelve tetrahydroindolizinoindoles, six tetrahydrocyclobutanindoloquinolizinones and three tetrahydrocyclopentenoneindolizinoindolones. These compounds were selected from a virtual combinatorial library of 11,478 compounds. Physical chemical properties were calculated and most of them are in accordance with Lipinski’s rules. Virtual docking and ligand-based target evaluations were performed for the β-carboline library compounds and selected synthetic intermediates to assess the therapeutic potential of these small organic molecules. These compounds have been deposited into the NIH Molecular Repository (MLSMR) and may target proteins such as histone deacetylase 4, endothelial nitric oxide synthase, 5-hydroxytryptamine receptor 6 and mitogen-activated protein kinase 1. These in silico screening results aim to add value to the β-carboline library of compounds for those interested in probes of these targets.
Keywords: β-carboline; biological activity; chemical diversity; diversity-oriented synthesis; in silico screening

(untitled) - Stockwell, B. R. (Nature, 2004)

NIH Common Fund Office of Strategic Coordination. Molecular Libraries and Imaging

(untitled) - Dandapani, S.; Marcaurelle, L. A. (Curr. Opin. Chem. Biol., 2010)

(untitled) - Painter, T. O.; Wang, L.; Majumder, S.; Xie, X.-Q.; Brummond, K. M. (ACS Comb. Sci., 2011)

(untitled) - Diness, F.; Beyer, J.; Meldal, M. (Chem.–Eur. J., 2006)

(untitled) - Siebert, M. R.; Osbourn, J. M.; Brummond, K. M.; Tantillo, D. J. (J. Am. Chem. Soc., 2010)

Modern Allene Chemistry - Murakami, M.; Matsuda, T. (Cycloaddition of Allenes, 2005)

(untitled) - Huryn, D. M.; Brodsky, J. L.; Brummond, K. M.; Chambers, P. G.; Eyer, B.; Ireland, A. W.; Kawasumi, M.; LaPorte, M. G.; Lloyd, K.; Manteau, B.; Nghiem, P.; Quade, B.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2011)

Maestro 8.5.207-QikProp, 2.1 (Schrödinger, LLC)
For calculations of physicochemical properties.

(untitled) - Lipinski, C. A.; Lombardo, F.; Dominy, B. W.; Feeney, P. J. (Adv. Drug Delivery Rev., 1997)

(untitled) - Kitchen, D. B.; Decornez, H.; Furr, J. R.; Bajorath, J. (Nat. Rev. Drug Discovery, 2004)

(untitled) - Berman, H. M.; Westbrook, J.; Feng, Z.; Gilliland, G.; Bhat, T. N.; Weissig, H.; Shindyalov, I. N.; Bourne, P. E. (Nucleic Acids Res., 2000)

(untitled) - Gao, Z.; Li, H.; Zhang, H.; Liu, X.; Kang, L.; Luo, X.; Zhu, W.; Chen, K.; Wang, X.; Jiang, H. (BMC Bioinformatics, 2008)

(untitled) - Jain, A. N. (J. Med. Chem., 2003)

(untitled) - Jain, A. N. (J. Comput.-Aided Mol. Des., 2007)

(untitled) - Martin, Y. C.; Kofron, J. L.; Traphagen, L. M. (J. Med. Chem., 2002)

(untitled) - Xie, X.-Q.; Chen, J.-Z. (J. Chem. Inf. Model., 2008)

(untitled) - Bender, A. (Nat. Chem. Biol., 2010)

(untitled) - Heikamp, K.; Bajorath, J. (J. Chem. Inf. Model., 2011)
Heikamp et al. carried out a large-scale similarity search investigation on 266 well-defined compound activity classes extracted from the ChEMBL database using molecular fingerprints. In 203 of 266 test cases (~76%), a compound recovery rate of at least 50% was observed.

(untitled) - Guha, R.; Howard, M. T.; Hutchison, G. R.; Murray-Rust, P.; Rzepa, H.; Steinbeck, C.; Wegner, J.; Willighagen, E. L. (J. Chem. Inf. Model., 2006)

(untitled) - Dhanak, D.; Christmann, L. T.; Darcy, M. G.; Jurewicz, A. J.; Keenan, R. M.; Lee, J.; Sarau, H. M.; Widdowson, K. L.; White, J. R. (Bioorg. Med. Chem. Lett., 2001)

(untitled) - Singh, I. P.; Jain, S. K.; Kaur, A.; Singh, S.; Kumar, R.; Garg, P.; Sharma, S. S.; Arora, S. K. (Eur. J. Med. Chem., 2010)

(untitled) - Srivastava, S. K.; Agarwal, A.; Chauhan, P. M. S.; Agarwal, S. K.; Bhaduri, A. P.; Singh, S. N.; Fatima, N.; Chatterjee, R. K. (J. Med. Chem., 1999)

(untitled) - Lippke, K. P.; Schunack, W. G.; Wenning, W.; Mueller, W. E. (J. Med. Chem., 1983)

(untitled) - Cole, D. C.; Lennox, W. J.; Stock, J. R.; Ellingboe, J. W.; Mazandarani, H.; Smith, D. L.; Zhang, G.; Tawa, G. J.; Schechter, L. E. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Cain, M.; Weber, R. W.; Guzman, F.; Cook, J. M.; Barker, S. A.; Rice, K. C.; Crawley, J. N.; Paul, S. M.; Skolnick, P. (J. Med. Chem., 1982)

(untitled) - Ksander, G. M.; de Jesus, R.; Yuan, A.; Ghai, R. D.; McMartin, C.; Bohacek, R. (J. Med. Chem., 1997)

(untitled) - Liu, J.; Jiang, X.; Zhao, M.; Zhang, X.; Zheng, M.; Peng, L.; Peng, S. (J. Med. Chem., 2010)

(untitled) - Mohamed, H. A.; Girgis, N. M. R.; Wilcken, R.; Bauer, M. R.; Tinsley, H. N.; Gary, B. D.; Piazza, G. A.; Boeckler, F. M.; Abadi, A. H. (J. Med. Chem., 2011)